Analisis Pola Grafik Candlestick pada Pergerakan EUR/USD - Cahyadi, Yoyo (Binus Business Review, 2012)
Candlestick chart is one of the charts which is commonly used in technical analysis. Besides for price overview in the past, this chart has patterns that can be analysed to become guidance about next price movement. There are some patterns with specific name in candlestick chart analysis. This paper discusses candlestick chart patterns in the EUR/USD currency pair within daily time frame. The observation shows that candlestick chart patterns indeed gave more guidance about trend changes. Although the candlestick patternsdid not show everyday, in most cases the patterns gave right guidance.